Protective Role of Cupressuflavone from Cupressus macrocarpa against Carbon Tetrachloride-Induced Hepato- and Nephrotoxicity in Mice - Al-Sayed, Eman; Abdel-Daim, Mohamed M. (Planta Medica, 2014)
The hepatoprotective and nephroprotective activity of cupressuflavone isolated from Cupressus macrocarpa was investigated against CCl4-induced toxicity in mice. Cupressuflavone was administered (40, 80, and 160 mg/kg/day) for five days. CCl4 was administered (0.5 mL/kg intraperitoneally) at the end of the experiment. A substantial increase (p < 0.001) in the levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, lactate dehydrogenase, total bilirubin, cholesterol, creatinine, uric acid, urea, and malondialdehyde was observed in the CCl4-treated group compared to the normal control group. In contrast, a significant reduction (p < 0.001) in glutathione and superoxide dismutase contents as well as the total protein level was evident in the CCl4-intoxicated mice. Cupressuflavone pretreatment markedly inhibited the CCl4-induced increase in alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, lactate dehydrogenase, cholesterol, creatinine, uric acid, urea, and malondialdehyde levels in a dose-dependent manner (p < 0.001 at all the tested doses). In addition, a significant (p < 0.001) and dose-dependent decrease in the total bilirubin levels was evident by cupressuflavone pretreatment (80 and 160 mg/kg/day) when compared to the CCl4-intoxicated group. Furthermore, cupressuflavone administration significantly increased the activity of antioxidant parameters glutathione and superoxide dismutase as well as the serum protein levels (p < 0.001 at all the tested doses) in a dose-dependent manner. Histological observations confirmed the strong hepato- and nephroprotective activity. These findings suggest that cupressuflavone could exert a beneficial effect against oxidative stress by enhancing the antioxidant defense status, reducing lipid peroxidation, and protecting against the pathological changes induced by CCl4 in the liver and kidney tissues. The structure of cupressuflavone was identified by NMR, UV, and HRESI-MS/MS spectral data.
Keywords: Cupressus macrocarpa; Cupressaceae; hepatoprotective; nephroprotective; biflavones; lipid peroxidation